Switches in histone modifications epigenetically control vitamin D3-dependent transcriptional upregulation of the CYP24A1 gene in osteoblastic cells - Moena, Daniel (J Cell Physiol, 2019)
In bone cells vitamin D dependent regulation of gene expression principally occurs through modulation of gene transcription. Binding of the active vitamin D metabolite 1,25(OH)(2)D(3) to the vitamin D receptor (VDR) induces conformational changes in its C-terminal domain enabling competency for interaction with physiologically relevant co-activators, including SRC-1. Consequently, regulatory complexes can be assembled that support intrinsic enzymatic activities with competency to post-translationally modify chromatin histones at target genomic sequences to epigenetically alter transcription. Here we examine specific transitions in representation and/or enrichment of epigenetic histone marks during 1,25(OH)(2)D(3) mediated upregulation of CYP24A1 gene expression in osteoblastic cells. This gene encodes the 24-Hydroxylase enzyme, essential for biological control of vitamin D levels. We demonstrate that as the CYP24A1 gene promoter remains transcriptionally silent, there is enrichment of H4R3me2s together with its “writing” enzyme PRMT5 and decreased abundance of the H3ac/H4ac, H3R17me2a, and H4R3me2a marks as well as of their corresponding “writers”. Exposure of osteoblastic cells to 1,25(OH)(2)D(3) stimulates the recruitment of a VDR/SRC-1 containing complex to the CYP24A1 promoter to mediate increased H3/H4 acetylation. VDR/SRC-1 binding occurs concomitant with the release of PRMT5 and the recruitment of the arginine methyltransferases CARM1 and PRMT1 to catalyze the deposition of the H3R17me2a and H4R3me2a marks, respectively. Our results indicate that these dynamic transitions of histone marks at the CYP24A1 promoter, provide a “chromatin context” that is transcriptionally competent for activation of the CYP24A1 gene in osteoblastic cells in response to 1,25(OH)(2)D(3).